Respostas

2013-11-16T17:07:59-02:00
3x-y=15               
-y=15-3x   (-1)
y=-15+3x

3x-y=15
-2x+3y=-3

-2x+3.(-15+3x)=-3
-2x-45+9x=-3
-2x+9x=-3+45
7x=42
x=42/7
x=6


y=-15+3x
y=-15+3.6
y=-15+18
y=3
1 5 1
2013-11-16T17:26:50-02:00
3x - y = 15
- 2x + 3y = - 3

y = 3x - 15
Substituido fica;
- 2x + 3 (3x - 15) = - 3
- 2x + 9x - 45 = - 3
- 2x + 9x = - 3 + 45
7x = 42
x = 42 : 7
x = 6
Substituindo o valor de x em uma das equações, encontraremos o valor de y:
3x - y = 15
Substituindo fica:
3 * 6 - y = 15
18 - y = 15
y = 18 - 15
y = 3

Resposta: 
x = 6
y = 3
1 3 1